RANCANG BANGUN SISTEM PENGENDALI SUHU, pH AIR DAN NUTRISI MENGGUNAKAN METODE FUZZY MAMDANI PADA TANAMAN HIDROPONIK PAKCOY - Bahtiar, Zuhrinada Alvin; Nurussa’adah, n/a; Nusantoro, Goegoes Dwi (Jurnal Mahasiswa TEUB, 2024)
Hydroponics is a cultivation system for plants that does not involve soil as a growing medium but rather utilizes alternative substrates such as perlite, vermiculite, gravel, sand, rice husks, and cocopeat, along with nutrient-rich water containing sufficient oxygen. One advantage of hydroponic techniques over soil-based agriculture is the relatively easier identification and monitoring of nutrient conditions. Unlike soil-based farming, which presents challenges in identifying soil types and their nutrient content, hydroponics offers a more straightforward approach. In the hydroponic cultivation of pakcoy, water quality stands as the primary parameter. To achieve optimal results, water conditions must maintain suitable temperatures, pH levels, and nutrient concentrations under the requirements for pakcoy growth. Designing a control system using the Mamdani fuzzy method will be implemented to regulate temperature, water pH, and nutrient concentration according to growth requirements to maintain water quality in pakcoy hydroponics. From the research findings, the device is capable of controlling water temperature in the hydroponic reservoir according to the desired setpoint membership function, ranging from 15°C to 30°C, with an average steady-state error of 2.16%. The device can regulate water pH according to the setpoint range of pH 5-7, with an average steady-state error of 2.6%. For nutrient concentration control, the device achieves the setpoint range of 1000-1200 ppm, with an average steady-state error of 1.15%. This study demonstrates that the Mamdani fuzzy logic-based control system for temperature, water pH, and nutrient concentration can enhance the growth of pakcoy hydroponics plants. Keywords: Hydroponics, Pakcoy, Water pH, Temperature, Nutrition, Fuzzy logic Mamdani